DEVELOPING PROBLEM SOLVING SKILLS FOR LIFELONG LEARNING THROUGH WORK-BASED LEARNING AMONG COMMUNITY COLLEGE STUDENTS - Wan Mohamed, Wan Azlinda; Omar, Badrul; Romli, Mohd Faroul Rafiq (Journal of Technical Education and Training, 2010)
Many training providers are working to improve their curricula to meet the demand of today’s industries. The Malaysian College Communities, one of the major providers for lifelong learning program, had introduced the Work-Based Learning (WBL) concept since 2007 to ensure that their graduates met these demands. One of the key skills required by industry is problem solving skill. The ability to solve a complex or an ill-structured work problem in the workplace is the kind of skill demanded at a high-level performance organization. This study investigates how the students rate their problem solving skills after undergoing WBL training. The Problem Solving Rating Scale for Employee (PSRS-E) questionnaire was used as the instrument for this study. Study shows that work-based learning may facilitate in developing the problem solving skills in students. Thus, the strengthening cooperation between industries and training institutions is essential in order to benefit students, the future workers of tomorrow.